Assessing lead sources in fishes of the northeast Pacific Ocean. (March 2020) - Li, Miling; Weis, Dominique; Smith, Kate E.; Shiel, Alyssa E.; Smith, Wade D.; Hunt, Brian P.V.; Torchinsky, Abe; Pakhomov, Evgeny A.
Graphical abstract: Abstract: Industrial lead (Pb) emissions have changed oceanic Pb concentrations and isotopic compositions significantly over the last century. Asian industrial emissions are currently the dominant Pb sources in the northwest and central Pacific Ocean. This study investigated major Pb sources in the northeast Pacific Ocean (inland, coastal, and open ocean), where no comprehensive data exist currently. We measured Pb concentrations and isotopic compositions of a variety of shellfish and fish collected in British Columbia (BC) and used them for Pb source apportionment applications in the marine environment. We identified a clear trend in Pb isotopic compositions, from higher 206 Pb/ 207 Pb in inland fish to lower 206 Pb/ 207 Pb in open ocean fish, with coastal fish possessing mid-range values. These results indicate that natural sources of Pb dominate freshwater ecosystems in the central BC coast, whereas anthropogenic Pb sources prevail in western North America and the northeast Pacific. Pacific herring that forage along BC coast exhibit Pb isotopic composition that deviates toward the Chinese Pb regression line. We estimate an Asian origin for about one third of their total Pb. This study shows that Pb isotopes in aquatic organisms are valuable tools for assessing Pb sources across coastal and offshore regions of the northeast Pacific, with great potential for identifying primary foraging areas of marine organisms.